Effects of Leader Narcissism on Career Success of Employees: An Interpersonal Relationship Perspective - Wang, Huaqiang; Li, Dan; Wu, Lei; Ding, Zhihui (Frontiers in Psychology, 2021)
Although previous studies have shown that leader narcissism has a significant impact on a leader’s effectiveness and employee behaviors, research on employees’ career outcomes is still inadequate. This study explores the impact of leader narcissism on employees’ career success from an interpersonal relationship perspective and examines the mediating role of supervisor-subordinate conflict and the moderating role of employee’s dominant personality traits. Data from 291 employees in Chinese companies have revealed that leader narcissism, directly and indirectly, affects employees’ career success through supervisor-subordinate relationship conflict. However, employees’ dominant personality traits strengthened the impact of leader narcissism on supervisor-subordinate relationship conflict. The theoretical and practical implications of our findings are further discussed.